The slightest gesture: deligny, the ritornello and subjectivity in socially just pedagogical praxis - van Heerden, Chantelle Gray (Education as change, 2017)
Positing existence in terms of difference and becoming as substantive, Gilles Deleuze and Félix Guattari are interested in ways of thinking and being that lie outside of institutionalised knowledge and the semiotic chains and regimes of power that sustain it. Although this line of thinking is not applied to pedagogy itself in a sustained manner in their work, their consideration of milieu and cartography, as related to subjectivity, can make an invaluable contribution to pedagogical praxis. In this paper, I diffractively read Deleuze and Guattari's thoughts on subjectivity through the writings and practices of Fernand Deligny. Like Deleuze and Guattari, Deligny was known for rejecting standardised forms of knowledge, instruction, and living, placing instead an emphasis on modes of being that lie outside the preexisting norms of the Symbolic Order and the dominance of language. It is, in part, from Deligny's practices that Deleuze and Guattari derived their method of cartography which can map subjectivity as "wander lines" and gestures within a social milieu. Together with territory, rhythm and the refrain ("ritournelle"), I think here about wander lines, gestures and milieu as part of a philosophical approach for effectuating socially just pedagogies in higher education, particularly in the context of the recent Fallist movement in South Africa.